2012
DOI: 10.1007/s10640-012-9567-1
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of Choice Experiments in Environmental Valuation

Abstract: The paper presents the results of the first test-retest study on choice experiments in environmental valuation. In a survey concerning landscape externalities of onshore wind power in central Germany, respondents answered the same five choice sets at two different points in time. Each choice set comprised three alternatives described by five attributes, and the time interval between the test and the retest was eleven months. The analysis takes place at three different levels, investigating choice consistency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 36 publications
5
50
1
Order By: Relevance
“…Fewer examinations of temporal stability of CE preferences and values have been undertaken, and none have examined long time periods. However, the existing studies tend to support stability of WTP values over short term periods of up to a year (Bliem et al, 2012;Liebe et al, 2012).…”
Section: Non-market Valuation Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Fewer examinations of temporal stability of CE preferences and values have been undertaken, and none have examined long time periods. However, the existing studies tend to support stability of WTP values over short term periods of up to a year (Bliem et al, 2012;Liebe et al, 2012).…”
Section: Non-market Valuation Methodsmentioning
confidence: 95%
“…If people's preferences and values for protecting TER marine species change over time, then using older value information in a benefits transfer will lead to biased results (i.e., increase the transfer error). In general, the empirical literature assessing the temporal stability of WTP estimates from SP studies, generally through test-retest samples or two independent samples engaged at different time periods, suggests that time periods up to about five years yield temporally stable preferences and values (e.g., Carson et al, 1997;McConnell et al, 1998;Brouwer and Bateman, 2005;Skourtos et al, 2010;Liebe et al, 2012) 29 . If one applies this rule of thumb to the literature examined here based on publication year, only eight studies (Lew et al, 2010;Ojea and Loureiro, 2010;Wallmo and Lew, 2011, 2012Boxall et al, 2012;Kontogianni et al, 2012;Stithou and Scarpa, 2012) comprise the set of viable studies that are recent enough to have preferences and values that are likely unchanged, but with several due to "expire" shortly.…”
Section: Applying Ter Marine Species Values To Policymentioning
confidence: 99%
“…Within the DCE literature, there areonly a few examples of the same respondents completing identical sets at different points in time 1 . Bryan et al (2000), Ryan et al (2006), San Miguel et al (2002 and Skjoldborg et al (2009) investigate the issue of intertemporal choice consistency within health DCE studies, while Liebe et al (2012), Schaafsma et al (2014) and Czajkowski et al (2014) do so in environmental contexts. The analytical focus of these papers is typically the level of choice consistency over time [in terms of raw counts or via measures of consistency, typically Cohen's statistic of inter-rater reliability (Cohen 1960)] and/or the stability of parameter estimates from choice models estimated on the pooled data.…”
Section: Information Effects and Intertemporal Choice Consistencymentioning
confidence: 99%
“…This indicated that there was no difference between preferences in these 30 samples. Liebe, Meyerhoff and Hartje (2012) used an Error Component model to compare preference 31 and WTP estimates in two samples collected 11 months apart. Choices over on-shore wind power 32 options were reasonably consistent over the interval, but WTP estimates differed significantly for around 33 half of the attribute values.…”
Section: Introductionmentioning
confidence: 99%